Diet Survey Of Icds Children In Pune City - Pratinidhi A.K; Tambe M.P; Garad S.G (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the protein & calorie intake of children getting supplementary nutrition under ICDS? Objectives: I) To study the protein and calorie intake of children covered under ICDS. ii) To study the protein & caloric content of supplementary nutrition. Study design: Cross- sectional. Setting: ICDS project of Pune city. Participants: Children aged 1-6 years, receiving supplementary nutrition from anganwadis. Sample size: 165 children aged 1-<6 tears. Study variables: Knowledge and perception of ICDS, Protein and calorie intake of children, nutritive value of ICDS supplementary foods. Results: There was a gross deficiency of proteins and calories in majority of the children. The protein and calorie intake was less than 50% of recommended daily allowance in 38.2% and 35.7% children respectively. Only 13.9% of children had a protein intake of Â³90% of RDA while 12.7% had a calorie consumption of Â³90% of RDA. 71.6% of children aged 3-<6 years took the food to their homes and shared with other family members thus depriving them the total benefit of supplementary nutrition. 46.1% mothers perceived the supplementary nutrition to be a substitude. The supplement given at anganwadi had an average nutritive value of 213 calories and 5.1 gm protein as compared to recommended values of 300 calories & 10 gms protein.